Language transfer as a communication strategy and a language learning strategy in a Malaysian ESL classroom. - Paramasivam, Shamala (Asian EFL Journal, 2009)
This paper reports on the use of language transfer as a type of communication strategy and language learning strategy drawing on a variety of oral interaction activities from a Malaysian classroom for English as a second language. The study provides insights into not only how the learners’ first language functions as a strategy for communication but also how it can enhance second language learning by way of helping learners expand their second language repertoire and increase their automatization of second language items.